Axiological foundation of the technological package as a pre-patentable basis for innovation in preventive functional bioproducts - Argota-Pérez, George (2025)
This study describes the axiological model of the technological package as a pre-patentable foundation of innovation, designed to articulate the value dimensions underpinning validation, transfer, and potential impact on preventive health. A descriptive, non-experimental study with a qualitative–analytical approach was conducted through structured documentary review and hermeneutic content analysis. The results present a systemic model that integrates ethical, technical, and social principles, structuring the innovation process from need identification to product commercialization and maintenance. This framework demonstrates that axiological coherence provides the technical robustness, sustainability, and social relevance required for responsible biotechnological innovation. The study concludes that the axiological foundation enables the transformation of scientific knowledge into pre-patentable value, establishing a replicable methodological framework for the development of functional bioproducts oriented toward disease prevention and the strengthening of public health through ethically grounded technological management.